FINANCING PATTERNS AND THEIR IMPACT ON INSTITUTIONAL DEBT - AN ECONOMETRIC STUDY USING PANEL DATA MODELS - Boussafsaf, Farid; Omane, Ahmed; Mosbah, Leila (The journal of contemporary issues in business and government, 2024)
This study aims to identify different financing patterns available to institutions, which can be categorised into three different patterns: self-financing, external financing through banking products and borrowing through the financial market. These patterns were considered as explanatory variables that were tested for their impact on the debt ratio, which was considered as the dependent variable. The study was conducted on a sample of five UAE institutions from 2013 to 2018. For this purpose, the standard econometric modelling approach using panel data models was applied. The statistical results indicated the acceptance of the random effects model at the 1% level of significance, reflecting the existence of a relationship between the explanatory variables representing funding patterns and the dependent variable representing the leverage ratio. In addition, a statistically significant negative effect of self-financing and external financing patterns on the debt ratio was found at the 1% level of significance.